Pemanfaatan Zeolit dan Arang Sekam sebagai Media Tanam Hidroponik Terapung dengan Pupuk Cair Kotoran Sapi - Ahmad Taofik; Setia Mulyawan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Red lettuce is a high-selling value leaf vegetable, especially as a result of organic cultivation. Organic red lettuce can be cultivated hydroponically and is increasingly growing and widespread in rural areas. In providing sufficient nutrients for organic systems cultivated through hydroponic methods, it is essential to provide nutrients from readily available sources, one of which is liquid fertilizer from cow dung. In addition to getting perfect nutrients, such as rice husk charcoal and zeolite, it dramatically affects plant growth. The study aims to determine the effect of using liquid organic fertilizer (LOF) from cow dung on the growth and yield of red lettuce in different growing media. The research was carried out at the screen house of the agrotechnology department at UIN Sunan Gunung Djati in 2021. Random Block Design is used as an experimental approach. A: Cow manure mixed with one hundred percent husk charcoal; B: Cow manure mixed with one hundred percent zeolite; and C: Cow manure mixed with fifty percent husk charcoal and fifty percent zeolite that make the treatment. The following variables were measured: plant height, number of leaves, leaf area, fresh weight, root shoot ratio, N content available in LOF, pH of the solution, and EC value. The study used an experimental random block design (RBD) approach, which included three treatments and seven replications. Each replication includes three plant units for a total of sixty-three test plants. After a 5% level variance analysis is performed on the data, a Duncan double-range test is performed if a difference is found. The findings show that red lettuce cultivated in a floating hydroponic system greatly benefits from the addition of LOF Cow Manure to other growing media in terms of growth and yield.